The Influence of Advertise E-Commerce Exposure in Mass Media and Intensity of Reading Consumer Testimonials on Internet to Level of Trust Online Transaction - Arribath Sakha; Dra. Sri Widowati Herieningsih, MS (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
This study aims to determine the effect of advertising exposure online trading site in the mass media and the intensity of consumer testimonials on the internet reading of the level of confidence to transact online. Its population is aged 18-35 audience ever seen ads online selling sites in the mass media and have read consumer testimonials on the Internet who live in Semarang. The sample of 60 respondents using non-probability sampling techniques. Data were collected using questionnaires filled out by respondents. Data were analyzed using regression analysis. Research findings indicate a positive and significant influence between advertising exposure online trading site in the mass media of the level of confidence to transact online. It is based on the value of regression coefficient of 0.771 which indicates that the higher the exposure to advertising buying and selling site online in the mass media, the higher the level of confidence to transact online. Furthermore, the results also showed a positive and significant influence between the intensity of consumer testimonials on the internet reading of the level of confidence to transact online. It is derived from the value of regression coefficient of 0.835, which means that the higher the intensity of consumer testimonials read on the internet, the higher level of confidence to transact online.